Duration and dispersion of QT interval in patients with liver cirrhosis: diagnostic and prognostic value - V. V. Genkel; V. N. Pospelov; A. S. Kuznetsova; N. V. Smagina; E. O. Vedernikova; S. M. Ashmarina; I. I. Shaposhnik (Сибирский научный медицинский журнал, 2025)
The data on the prognostic significance and relationship of the prolonged QT syndrome with the risk of cardiac rhythm disturbances in liver cirrhosis are contradictory. One of the directions of further research in this area is to study the significance of other electrocardiographic parameters reflecting ventricular repolarization disturbance in patients with liver cirrhosis.   Aim of the study was to investigate diagnostic and prognostic value of electrocardiographic parameters reflecting changes in heart electrical systole and heterogeneity of ventricular repolarization in relation to the presence of terminal liver cirrhosis and development of adverse outcomes in patients with established diagnosis of liver cirrhosis.   Material and methods. The study included 35 patients with an established diagnosis of liver cirrhosis and 20 comparison group individuals matched by gender (p = 0.550) and age (p = 0.376). The severity of liver cirrhosis was assessed using the MELD and Child-Turcotte-Pugh scales. All patients had ECG recorded and analyzed on a Poli-Spectrum-8/E electrocardiograph (Neurosoft LLC, Ivanovo).   Results. Patients with liver cirrhosis had significantly longer QTc interval durations than those in the comparison group (458.0 [432.5; 482.7] and 418.5 [405.0; 432.0] ms, respectively) (median [25th percentile; 75th percentile]) and smaller absolute and relative to QT interval Tpeak-Tend interval values. The severity of liver cirrhosis, as determined by the MELD scale, was directly correlated with QTc (r = 0.355; p = 0.0396), QTd (r = 0.389; p = 0.0228) and QTcd (r = 0.382; p = 0.0257) interval duration. The follow-up period was 3.96 [1.50; 8.59] months. Death from cirrhosis-related causes was recorded in 12 (34.3 %) patients. Among the electrocardiographic parameters investigated, the addition of QTc interval duration to the MELD scale in the prognostic model made it possible to increase the model performance and achieve statistical significance (area under the curve 0.763 (95 % confidence interval 0.633–0.894), p = 0.0088).   Conclusions. Patients with liver had higher QTc values than those in the comparison group and lower Tpeak-Tend, Tpeak-Tend/QT and Tpeak-Tend/QTc values. The severity of liver cirrhosis, as determined by the MELD scale, was associated with an increase in QTc, QTd and QTcd duration. Adding QTc interval duration to the MELD scale allowed for the increase in the performance of the all-cause mortality prediction model.